2020
DOI: 10.1002/jee.20345
|View full text |Cite
|
Sign up to set email alerts
|

Research literature on women of color in undergraduate engineering education: A systematic thematic synthesis

Abstract: BackgroundTo address social disparities and generate an innovative workforce, engineering higher education should provide learning environments that benefit students from all backgrounds. However, because engineering programs are not enrolling or retaining women of color at demographic parity, a better understanding of these students' experiences is needed to develop effective interventions.PurposeThis study analyzes research on women of color in undergraduate engineering education to determine what influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 74 publications
1
117
1
Order By: Relevance
“…Researchers have found unique challenges among racially minoritized women 2 undergraduates in engineering (Ong et al, 2020;Ro & Loya, 2015), physics (Ko et al, 2013;Ong, 2005), computer science (Ong, 2011), and mathematics (Borum & Walker, 2012), or STEM in general (Ong et al, 2018). While these researchers explored sub-STEM disciplines, they nevertheless found several common themes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found unique challenges among racially minoritized women 2 undergraduates in engineering (Ong et al, 2020;Ro & Loya, 2015), physics (Ko et al, 2013;Ong, 2005), computer science (Ong, 2011), and mathematics (Borum & Walker, 2012), or STEM in general (Ong et al, 2018). While these researchers explored sub-STEM disciplines, they nevertheless found several common themes.…”
Section: Discussionmentioning
confidence: 99%
“…Although interest is emerging in women of color undergraduates in STEM fields (Ong et al, 2020), so far existing studies have focused on the impact of individual, disciplinary, or institutional characteristics on their success. Few studies address whether the local supply of colleges relates to student success among women of color as measured by STEM bachelor's degree attainment at a community level with respect to the "geography of educational opportunity" .…”
Section: Discussionmentioning
confidence: 99%
“…For this study, race is defined as a social construct that categorizes humans based on shared physical or social qualities into distinct groups (Barnshaw, 2008). The control of race was needed because existing studies showed that race is an important factor that affects labor market outcomes in the engineering occupation (Ong et al, 2020) and geographic location of the job (1 = Ontario /0 = rest of Canada ) (The coding of Ontario Province versus the rest of Canada was made to reflect the 2008/2009 loss of the automotive sector, which employed many engineers in the province). I also constructed and tested several interaction terms to assess their effect on the duration of the search for the first job.…”
Section: Methodsmentioning
confidence: 99%
“…Critical scholars had for decades argued against this perceived meritocracy, critiquing Western science and engineering (Franklin, 1985 ; Haraway, 1996 ; Harding, 1986 ; Seron et al, 2018 ; Slaton & Pawley, 2018 ). These critiques have been seen in practice in research showing sexism (Blickenstaff, 2005 ; Hunt, 2016 ; Logel et al, 2007 ), homophobia (Cech & Rothwell, 2018 ; Cech & Waidzunas, 2011 ; Hughes, 2017 ) and anti-Black racism (Blosser, 2020 ; Fletcher et al, 2017 ; McGee & Martin, 2011 ; Ong et al, 2020 ) in engineering. However, the attitude is that race is not relevant in engineering and the mindset of equality over equity persists.…”
Section: Barriers To Implementationmentioning
confidence: 99%
“…In the USA, more work has been done to understand how racism manifests in engineering education. Although not always explored through CRT, much of the literature highlights the inequities that exist for Black (Berhane et al, 2020 ; Blosser, 2020 ; McGee & Martin, 2011 ), Indigenous (Page-Reeves et al, 2018 ) and other racialized students (McGee et al, 2017 ; Ong et al, 2020 ; Ro & Kim, 2019 ) in engineering programmes. However, within the Canadian context, there is limited available literature providing critical reflections at the intersection of post-secondary STEM education, institutional operations and race-based considerations, particularly in the context of engineering education and Black inclusivity.…”
Section: Introductionmentioning
confidence: 99%